Innovation and Nanotechnology - Koepsell, David (Bloomsbury Academic, 2011)
This book defines 'nanowares' as the ideas and products arising out of nanotechnology. Koepsell argues that these rapidly developing new technologies demand a new approach to scientific discovery and innovation in our society. He takes established ideas from social philosophy and applies them to the nanoparticle world. In doing so he breaks down the subject into its elemental form and from there we are better able to understand how these elements fit into the construction of a more complex system of products, rules and regulations about these products. Where existing research in the field has tended to focus on potential social harm, Koepsell takes a different approach by looking at ways in which developments in distributed design and fabrication can be harnessed to enable wealth creation by those with good ideas but no access to capital. He argues that the key challenge facing us is the error implicit in current intellectual property regimes and presents new modes of relating inventors to artifacts in this new context. In conclusion he offers contractual models which he believes encourage innovation in nano-media by embracing open source and alternative means of protection for innovators.